COMPARISON OF THE GRAMMATICAL CATEGORY OF VERB MOOD IN RUSSIAN AND UZBEK LANGUAGES - Rustamova Malika Nuralievna (Western European Studies, 2025)
The category of verb mood is an integral part of the grammatical system of any language and performs a critical communicative-pragmatic function. It reflects the speaker's subjective attitude towards the action - its reality, desirability, presumption, or possibility of implementation. In this sense, mood is closely related to grammatical and semantic categories such as modality, tense, aspect, and person
Keywords: tense; implementation; closely